The Threat Of New Security Alliances In The Indo-pacific Region To The Centralization Of Asean: The Case Of Aukus - Fellah, Amina (المجلة الجزائرية للأمن الإنساني, 2022)
Since its creation, the ASEAN try hard to hold a central position in both the regional security architecture and the economic cooperation in the region. Nonetheless, the US participates in the security alliance along with Australia, and the UK, or what is known as AUKUS unquestionably dethrone ASEAN’s centrality in terms of regional decision-making in the East Asian and Indo-Pacific regions. The central research question of the paper is to understand how the new security alliances in the Indo-Pacific region weaken ASEAN’s centrality in regional affairs. To explain the research question, this paper takes AUKUS as a case study. The paper using the networking analysis, argues that the US’s way of consolidating and broadening its alliances is by networking with and between allies, through an integrated deterrence concept and networked approach, which is threatening the notion of ASEAN centrality. The main paper’s findings are that the AUKUS will further weaken the already deterioration of ASEAN centrality’s efforts to handle its own interior affairs. Southeast Asia states differing stances on AUKUS present deeper problems for ASEAN’s centrality future. Also, AUKUS outlines the US restructuring its ‘hubs and spokes’ alliance system through an “integrated deterrence” strategy and network approach in the Indo-Pacific region.